The effect of worker behavior and physical workload on work productivity through blood pressure of workers at PT Maruki International Indonesia - Bidiastuti, Feiby; Wahyu, Atjo; Russeng, Syamsiar S.; Thamrin, Yahya; Salmah, Ummu (Edelweiss Applied Science and Technology, 2026)
This study examines how physical workload, smoking, and coffee intake affect blood pressure and employee productivity. A quantitative research approach was employed, with data obtained from 147 respondents using questionnaires and blood pressure assessments. The results of the analysis showed that physical workload had a significant positive effect on systolic blood pressure (p=0.001; β=0.264) and a significant negative effect on work productivity (p=0.003; β=-0.166), but not significantly on diastolic blood pressure (p=0.082). Smoking behavior had a significant positive effect on systolic blood pressure (p=0.020; β=0.191) and diastolic blood pressure (p=0.001; β=0.249), but not significantly on work productivity (p=0.092). Coffee drinking behavior showed a significant positive effect on systolic blood pressure (p=0.037; β=0.186) and diastolic blood pressure (p=0.014; β=0.239), and through blood pressure had a significant effect on work productivity. In addition, systolic (p=0.037; β=-0.212) and diastolic (p=0.000; β=-0.372) blood pressure had significant negative effects on work productivity. These findings emphasize the need to manage workload and caffeine intake to support heart health and productivity. The management of PT Maruki International Indonesia should regulate physical workload as well as employees’ smoking and coffee consumption habits through workplace health policies to maintain healthy blood pressure and improve work productivity.